The Dynamics of Kafa’ah Nasab and the Identity of Sharifah Women: An Examination of Sayyid Utsman's Perspectives within the Context of Gender Equality - Nouvaldi, Ahmad Azzam; Widigdo, Mohammad Syifa Amin (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2025)
This research examines the concept of equality of status (kafâ'ah nasab) in marriage, particularly within the family community of habaib descendants (sayyid and sharifah). The study is approached through the lens of Sayyid Utsman bin Yahya's thoughts and is contextualised within the framework of gender equality studies. Within the habaib tradition, marriages between a sharifah and a non-sayyid man are frequently rejected on the grounds of perceived deficiencies in lineage, and such unions are often deemed to contravene social and religious norms. Sayyid Uthman, a prominent scholar of the Dutch East Indies colonial period, underscored the invalidity of such marriages in several of his works, which subsequently became significant references in the social structure of the habaib community. However, from a gender equality standpoint, this practice raises issues of discrimination against women and reinforces a patriarchal system rooted in lineage. This research employs a qualitative approach, utilising literature review methods and interviews with Rabithah Alawiyah. The findings indicate that, in practice, kafâ'ah nasab has evolved into a mechanism of social control that restricts women's autonomy in selecting a life partner and perpetuates inequality in gender relations. Consequently, a reinterpretation of this concept is necessary to align it with Islamic sociology and the principles of justice inherent in Islam.